2019
DOI: 10.1097/md.0000000000016431
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of β-endorphin concentration, mood, and pain intensity in men with idiopathic hip osteoarthritis treated with variable magnetic field

Abstract: Osteoarthritis is the most frequently diagnosed disease of the musculoskeletal system. Growing number of patients waiting for surgical treatment and the possible negative consequences resulting from long-term pharmacological therapy lead to the search for non-pharmacological methods aimed at alleviating pain and reducing doses of analgesics, among them physical therapy with use of magnetic fields. The study involved 30 men aged 49 to 76 (mean age, 61.7 years) treated for idiopathic osteoarthritis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Moreover, some clinical researches showed that higher plasma BE predicts greater subsequent acute pain intensity and that higher BE levels could be a marker for enhanced endogenous opioid analgesia. [27,28] The mechanism of how magnesium exerts it analgesic action is still unclear. A popular theory is that the anti-nociceptive actions is the result of its inhibition of the NMDA receptor.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, some clinical researches showed that higher plasma BE predicts greater subsequent acute pain intensity and that higher BE levels could be a marker for enhanced endogenous opioid analgesia. [27,28] The mechanism of how magnesium exerts it analgesic action is still unclear. A popular theory is that the anti-nociceptive actions is the result of its inhibition of the NMDA receptor.…”
Section: Discussionmentioning
confidence: 99%
“…Also, its benefits on pain and joint stiffness at the cellular-molecular level have been shown. (Kurt et al 2016 ; Koczy et al 2019 ; Fioravanti et al 2011 ), Balneotherapy provides analgesic effects by preventing the stimulation of nociceptive receptors, reducing pain transmission through the gate control theory of pain stimulating thick nerve-fibers, removing oxygen radicals, and increasing beta-endorphin levels in particular (Yurtkuran et al 1993 ; Koczy et al 2019 ; Tishler et al 2004 ; Bender et al 2005 ; Hizmetli and Hayta 2011 ). Again in the literature, it has been shown that balneotherapy treatments decrease inflammation and, ultimately, pain by increasing anti-inflammatory cytokines (Shehata et al 2006 ).…”
Section: Discussionmentioning
confidence: 99%